Assessment of estrogenic activity in PM10 air samples with the ERE-CALUX bioassay: Method optimization and implementation at an urban location in Flanders (Belgium). (February 2016) - Croes, Kim; Debaillie, Pieterjan; Van den Bril, Bo; Staelens, Jeroen; Vandermarken, Tara; Van Langenhove, Kersten; Denison, Michael S.; Leermakers, Martine; Elskens, Marc
Abstract: Endocrine disrupting chemicals represent a broad class of compounds, are widespread in the environment and can pose severe health effects. The objective of this study was to investigate the overall estrogen activating potential of PM10 air samples at an urban location with high traffic incidence in Flanders, using a human in vitro cell bioassay. PM10 samples (n = 36) were collected on glass fiber filters every six days between April 2013 and January 2014 using a high-volume sampler. Extraction was executed with a hexane/acetone mixture before analysis using a recombinant estrogen-responsive human ovarian carcinoma (BG1Luc4E2) cell line. In addition, several samples and procedural blanks were extracted with ultra-pure ethanol or acetonitrile to compare extraction efficiencies. Results were expressed as bioanalytical equivalents (BEQs) in femtogram 17β-estradiol equivalent (fg E2-Eq) per cubic meter of air. High fluctuations in estrogenic activity were observed during the entire sampling period, with mean and median BEQs of 50.7 and 35.9 fg E2-Eq m − 3, respectively. Estrogenic activity was measured in more than 70% of the samples and several sample extracts showed both high BEQs and high cytotoxicity, which could not be related to black carbon, PM10 or heavy metal concentrations. At this moment, it remains unclear which substances cause this toxicity, but comparison of results obtained with different extraction solvents indicated that acetone/hexane extracts contained more compounds that were cytotoxic and suppressive of responses than those extracted using ultra-pure ethanol. Although more research is needed, the use of a more polar extraction solvent seems to be advisable. Highlights: We measured the overall estrogenic activity of PM10 in Flanders. The human ovarian BG1Luc4E2 bioassay (ERE-CALUX) was used. Estrogenic activity was low, but quantifiable in more than 70% of the samples. Acetone/hexane extracts more cytotoxic compounds than ethanol or acetonitrile. Use of a more polar extraction solvent is advisable.